The woman in suite 11 - Ware, Ruth (Scout Press, 2025)
"When the invitation to attend the press opening of a luxury Swiss hotel -- owned by reclusive billionaire Marcus Leidmann -- arrives, it's like the answer to a prayer. Three years after the birth of her youngest child, Lo Blacklock is ready to reestablish her journalism career, but post-pandemic travel journalism is a very different landscape from the one she left ten years ago. The château on the shores of Lake Geneva is everything Lo's ever dreamed of, and she hopes she can snag an interview with Marcus. Unfortunately, he proves to be even more difficult to pin down than his reputation suggests. When Lo gets a late-night call asking her to come to Marcus's hotel room, she agrees despite her own misgivings. She's greeted, however, by a woman claiming to be Marcus's mistress, and in life-or-death jeopardy. What follows is a thrilling cat-and-mouse pursuit across Europe, forcing Lo to ask herself just how much she's willing to sacrifice to save this woman...and if she can even trust her." --